HPLC in enzymatic analysis - Rossomando, Edward F (Wiley, 1998)
High performance liquid chromatography (HPLC) is a widely-used laboratory technique. In the second edition of this book, the author describes refinements of HPLC methods and explains and illustrates a range of laboratory applications.